PENGARUH AKREDITASI RUMAH SAKIT TERHADAP MUTU PELAYANAN KESEHATAN: LITERATURE REVIEW - Mochammad Malik Ibrahim; Azka Himatul Ulya; Cahya Arum Yuwantika; Muhammad Arika; Ria Irmanda Putri Melani; Rizkynieta Dwi Impiyani; Wulan Ayu Puspita (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2022)
The implementation of hospital accreditation is a policy used to measure whether the standards set by the government have been met by a hospital, besides that another function of hospital accreditation is that it can be used as an accountability for the quality of services provided. This study aims to determine whether there is an influence between hospital accreditation and the quality of health services. Literature Review design was chosen as the design to conduct this research, the databases used are Elsevier, google scholar, PubMed, and Sinta. Hospital accreditation has an influence on the quality of service in the hospital, where the higher the accreditation of a hospital, the better the quality of health services. There are several factors that can improve both variables, including the use of information technology, patient assessment, drug use management, patient and family education, control and prevention of infectious diseases, facility management.